Kinetics of hydrogen permeation through a Ni-base alloy membrane exposed to primary medium of pressurized water reactors. (November 2018) - Marchetti, Loïc; Martin, Frantz; Datcharry, Frédéric; Chêne, Jacques
Highlights: In situ hydrogen permeation measurement through Ni-base alloy in PWR primary medium. Hydrogen uptake kinetic modelling correlated with oxide scale growth. High surface hydrogen activities associated with initial oxidation stage. Hydrogen participation to stress corrosion cracking mechanisms suggested. Abstract: Hydrogen permeation kinetics through a Ni-base alloy exposed to simulated pressurized water reactors primary medium at 325 °C has been investigated. In situ measurements exhibit a strong decrease of H flux during the first 50 h of exposure; it has been related to the oxide scale growth at the alloy surface. A kinetic model has been proposed to describe this link. Comparing modelling and experimental results indicates that high H transient activities are generated at the alloy surface during the first hours of oxide scale growth, suggesting that H could play a role in stress corrosion cracking of Ni-base alloys.